Effect of Light-Emitting Diode Phototherapy on Allograft Bone After Open Sinus Lift Surgery: A Randomized Clinical Trial (Concurrent Parallel): LED Effect on Sinus Lift - Arshad, Mahnaz; Ghanavati, Zahra; Aminishakib, Pouyan; Rasouli, Kamran; Shirani, Gholamreza (Journal of Lasers in Medical Sciences, 2021)
Introduction: Phototherapy with a light-emitting diode (LED) is used in medicine due to its potential bio-stimulatory effects on the human body. However, controversy still exists regarding the efficacy of low-level laser therapy (LLLT) and phototherapy with LED. This in vivo study aimed to quantitatively and qualitatively assess the newly formed bone following LED phototherapy of the human maxillary sinuses. Methods: This randomized clinical trial (concurrent parallel) was conducted on 44 patients in two groups (n=22) at the Implant Department of Tehran University of Medical Sciences. Randomization was done by a random sequence generator program. The inclusion criteria were the absence of chronic sinusitis and chronic bone marrow conditions, no history of surgery at the site, absence of diabetes mellitus, no history of chemotherapy or radiotherapy, maxillary premolar edentulism, and signing informed consent forms. Group A underwent LED phototherapy with 620 ± 2 nm wavelength for 20 minutes daily for a total of 21 days after sinus lift surgery. Group B served as the control group and did not receive phototherapy. After 6 months, the grafted sites were re-opened for implant placement, and bone biopsy samples were obtained using a trephine bur. The samples were stained with hematoxylin and eosin and inspected under a light microscope. The results were statistically analyzed using the Mann-Whitney U test. Both the surgeon and pathologist were blinded to the group allocation of patients. Results: Forty tissue specimens were analyzed. Insignificant differences existed between the two groups in terms of the degree of inflammation, bone quality, and maturity of collagen. Histological analyses revealed no significant difference in the mineralized areas of bone between the two groups (P>0.05). Conclusion: The results indicated that LED phototherapy cannot significantly enhance osteogenesis after sinus lift surgery. No side effects were observed in the experimental group. DOI: 10.34172/jlms.2021.16